ANALISIS PERSEPSI DEVELOPER TERHADAP PRODUK KREDIT PEMILIKAN RUMAH (KPR) BANK XYZ CABANG BOGOR - Yuni Krisnawati; Kirbrandoko Kirbrandoko; MD. Djamaludin (School of Business, Bogor Agricultural University (SB-IPB), 2009)
The result of the study showed that respondent had difference perception about Bank XYZ Housing loan (KPR) product and other bank. There are eleven attributes as respondent factors in choosing Housing loan (KPR) product applied in this research, the attributes are interest rate, term and conditions loan, down payment, fees and chargers, credit process, product information, services from account officer, sales fee (commision), event of gathering and bank location. According to perception of respondent there are five excellences of mortgage product Bank XYZ, that is having term loan that is sufficiently long, down payment which is light, credit process that is quickly, event of gathering which is good enough and good location. Bank XYZ need strategy to increase Housing loan product, such as increase sales fee or reward to sales developer by giving special program and interesting reward, gives service marketing satisfying, competing interest rate, Meanwhile the management has to maintains good enough have been credit process and more improved again, because according to perception of respondent a real important attributes are sales fee for sales developer, interest rate and credit process. That attributes also becomes main preference according to respondent perception.